ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN MUATAN LOKAL BAHASA INGGRIS KELAS V DI MI JAM'IYATUL ISLAMIYAH DASAN BARU - Riza Indiriyani; Siti Nurul Fitriani; Marudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the learning difficulties experienced by elementary school students in the local content subject of English. As a foreign language, English requires mastery of listening, speaking, reading, and writing skills, which often pose challenges for students due to limited vocabulary, lack of learning media, and low learning motivation. The literature review of this study draws on behaviorist, cognitive, constructivist, humanist, and Gestalt theories, which emphasize the importance of motivation, learning environment, and teaching methods in supporting successful learning outcomes. The research employed a descriptive qualitative method, with the subjects being fifth-grade students of MI JMI Jami’atul Islamiyah Dasan Baru. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing, with triangulation techniques applied to ensure data validity. The results indicate that students face difficulties in mastering vocabulary, grammar, pronunciation, and reading and writing skills. The main contributing factors include a lack of learning media, low motivation, limited environmental support, and less engaging teaching methods. The study concludes that these learning difficulties negatively impact students’ academic outcomes and recommends the need for more varied and interactive learning strategies and media